EFFECTIVENESS OF MEDIAL TO LATERAL TAPING WITH EXERCISE PROGRAMME IN SUBJECTS WITH LATERAL EPICONDYLITIS (International Journal of Physiotherapy, 2014)
Background: Medial to lateral tapping and exercise programme has been found to be effective in Lateral epicondylitis. The purpose to find the combined effect of Medial to lateral tapping with exercise programme for subjects with lateral epicondylitis on pain intensity and functional ability.Method: An experimental study design, selected 40 subjects with Lateral epicondylitis randomized 20 subjects each into Study and Control group. Control group received only exercise programme while study group received combined medial to lateral tapping with exercise programme thrice a week for 4 weeks. Pain intensity was measured using Visual analogue scale and functional ability was measured using Patient Rated Tennis Elbow Evaluation questionnaire before and after 4 weeks of treatment.Results: When the post-intervention means were compared between Study and Control group after 4 weeks of treatment found statistically significant difference in the improvement in outcomes measures in means of VAS and PRTEE before and after intervention within the groups.Conclusion: It is concluded that the Medial to lateral tapping with exercise programme is more effective than the exercise programme in reduction of pain and improve functional abilities for subjects with Lateral epicondylitis.